Analysis for Heart Related Issues using comprehensive Approaches: A Review - Nirmala, Kumari; Singh, RM; Gupta, Shilpi (International Journal of Computer Sciences and Engineering, 2015)
Nowadays the heart problems are like one of the common things that are happening throughout the world. There are various reasons that lead to heart diseases problems, and the most common among is the change in lifestyle. For doctors it becomes quite tedious task to identify and rectify disease as there are thousands of symptoms that are held responsible for it. Comprehensive study of various machine learning approaches like various supervised and unsupervised algorithm like neural network, Genetic algorithm as well as Data mining approaches are covered in this paper which are helpful in early prediction of heart diseases so that many lives could be saved. Other approaches are also discussed in this paper that help in early prediction of heart disease e.g. with the help of speech analysis and also with the help of Big Data.